2013
DOI: 10.1210/jc.2012-2874
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Light at Night, Nocturnal Urinary Melatonin Excretion, and Obesity/Dyslipidemia in the Elderly: A Cross-Sectional Analysis of the HEIJO-KYO Study

Abstract: Exposure to LAN in an uncontrolled home setting is associated with impaired obese and lipid parameters independent of nocturnal urinary melatonin excretion in elderly individuals. Moreover, LAN exposure is associated with higher ORs for obesity and dyslipidemia independent of demographic and socioeconomic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 42 publications
7
117
2
1
Order By: Relevance
“…Based on our present data, the daily light exposure may thus well explain the circannual cycle of BAT detectability. Similarly, impaired BAT activity may also explain, at least partly, the relationship between obesity and disturbances in circadian rhythmicity in humans by light pollution (2,3,34), and possibly also by shift work (35)(36)(37) and sleep curtailment (1,38,39). Additionally, our data may provide the link in the relationship between exposure to light in the bedroom and obesity (4).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Based on our present data, the daily light exposure may thus well explain the circannual cycle of BAT detectability. Similarly, impaired BAT activity may also explain, at least partly, the relationship between obesity and disturbances in circadian rhythmicity in humans by light pollution (2,3,34), and possibly also by shift work (35)(36)(37) and sleep curtailment (1,38,39). Additionally, our data may provide the link in the relationship between exposure to light in the bedroom and obesity (4).…”
Section: Discussionmentioning
confidence: 67%
“…M odern world society is subjected to disturbances of circadian rhythms by shift work, sleep deprivation, and environmental light pollution. Importantly, the increasing prevalence of obesity is associated with a disrupted sleep-wake pattern in humans (1) and coincides with the availability of artificial light (2,3). Additionally, a recent study revealed a relationship between exposure to light at night and obesity in a cross-sectional analysis of over 100,000 women (4).…”
mentioning
confidence: 99%
“…In the home setting, bedroom light intensity had a positive correlation with the prevalence of obesity (109,110) and evening artificial light intensity showed a positive correlation with the incidence of type 2 diabetes (111) . Furthermore, daytime light exposure was positively correlated with BMI (112) .…”
Section: Effect Of Light On Food Intake Body Weight and Glucose Metamentioning
confidence: 99%
“…These include light at night (37,68), study-associated stress or interindividual differences in basal stress levels or stress tolerability (e.g., via effects on cortisol and sympathetic activity) (18,69), lifestyle factors of the participants, sedentary versus mobile state (9), and ambient temperature (70). As an example, environmental temperature can affect energy expenditure under both sedentary and active conditions (71).…”
Section: Experimental and Environmental Conditionsmentioning
confidence: 99%